The cost of using cash and checks in Uruguay - Marcelo Álvez; Rodrigo Lluberas; Jorge Ponce (Journal of Central Banking Theory and Practice, 2020)
The incorporation of new technologies to financial activities implies challenges and opportunities to financial authorities. They are reacting to the unavoidable trend towards digitalization of financial activities with the objective of preserving stable and efficient payment and financial systems. Uruguay, for instance, has promoted the use of electronic payment instruments and tested in the real economy a central bank digital currency called e-Peso. Digitalization of payment systems would reduce transaction costs by (partially) replacing less efficient means of payment, e.g. paper-cash and checks. In this paper we find that the cost of using cash in Uruguay is approximately 0.61% of GDP. Interestingly, 98.1% of this cost is borne by the private sector: banks and retailers 77.1% and households 21.0%. The cost of using checks is equivalent to 0.04% of GDP. Overall, replacing paper-cash and checks by other (electronic) means of payment would imply a transaction cost reduction for the private sector of the equivalent of up to 0.65% of GDP.
Keywords: D12; D23; D24; 330; payment system; cost of cash; cost of checks; electronic payments